School mental health promotion and intervention: Experiences from four nations. (August 2017) - Weist, Mark D.; Bruns, Eric J.; Whitaker, Kelly; Wei, Yifeng; Kutcher, Stanley; Larsen, Torill; Holsen, Ingrid; Cooper, Janice L.; Geroski, Anne; Short, Kathryn H.
All around the world, partnerships among schools and other youth-serving systems are promoting more comprehensive school-based mental health services. This article describes the development of international networks for school mental health (SMH) including the International Alliance for Child and Adolescent Mental Health and Schools (INTERCAMHS) and the more recent School Mental Health International Leadership Exchange (SMHILE). In conjunction with World Conferences on Mental Health Promotion, SMHILE has held pre-conference and planning meetings and has identified five critical themes for the advancement of global SMH: 1) Cross-sector collaboration in building systems of care; 2) meaningful youth and family engagement; 3) workforce development and mental health literacy; 4) implementation of evidence-based practices; and 5) ongoing monitoring and quality assurance. In this article we provide general background on SMH in four nations, two showing strong progress (the United States and Canada), one showing moderate progress (Norway), and one beginning the work (Liberia). Following general background for each country, actions in relation to the SMHILE themes are reviewed. The article concludes with plans and ideas for future global collaboration towards advancement of the SMH field.